Territorios del trauma: terrorismos y narrativa hispanoamericana actual - Jastrzębska, Adriana Sara (Studia Romanica Posnaniensia, 2015)
In Colombia and Central America, the subject of terrorism – or of the acts of terror – is inevitable in all the literature that aspires to reflect the socio-political reality. In the last few years it has been given an exceptional importance. Taking as the basis various examples of the modern Colombian and Central American narrative, the article presents distinct ways in which the novels try to deal with the trauma of the recent history. The analyzed works are Los ejércitos by E. Rosero, Insensatez by H. Castellanos Moya and El material humano by R. Rey Rosa. The analysis focuses on how the tragic experiences of the common people are absorbed by the narrative, turning trauma into literature. We are particularly interested in a meta-literary reflection regarding social commitment of literature, as well as the impossibility of dealing with trauma and the relations between the esthetic and ethical values in literary representations of trauma.